ARTIFICIAL INTELLIGENCE-ASSISTED CRITICAL AND REFLECTIVE THINKING DESIGN - Adam Fernando; Diah Putri Anggun; Diandara Oryza (Seminar Nasional Pendidikan IPA Ke III Tahun 2025, 2025)
The current development of artificial intelligence technology demands that everyone improve their critical and reflective thinking skills. Therefore, efforts are needed to prevent weakening human thinking skills due to dependence on this technology. This research aims to describe a critical and reflective thinking design framework suitable for applying artificial intelligence technology in the biology learning process. It was conducted through a literature review related to this topic. Based on the results obtained, there are eight elements of a critical and reflective thinking design framework for applying artificial intelligence technology.